Determinants of Consumer Satisfaction and Revisit Intention in Culinary Tourism - Elistia Elistia; Putra Maulana (President University, 2023)
Culinary tourism is one of the main components of tourist behavior towards specific destinations where experience local food, one part of Indonesian culinary tourism that can attract tourists is Bandung, West Java. This study aims to analyze the determinants of Customer Satisfaction and Revisit Intention, which are influenced by Food Quality, Price Fairness, and Physical Environment factors in culinary tourism in Braga, Bandung, West Java. This quantitative research method uses a descriptive causality approach with a sample of 200 respondents. Data collection using online surveys is processed and analyzed using the Structural Equation Model. The results of this study show that Physical Environment has a positive effect on Customer Satisfaction. However, Food Quality and Price Fairness do not positively affect Customer Satisfaction. Factors that positively affect Revisit Intention are Food Quality and Customer Satisfaction, but on the contrary, Physical Environment does not significantly affect Revisit Intention. Research findings show that Customer Satisfaction can significantly mediate the influence between Physical Environment and Revisit Intention. Furthermore, the results show that Customer Satisfaction can increase Revisit Intention. Thus, Food Quality and Price Fairness are concerns for culinary business actors in Braga, Bandung, to evaluate prices and food offered so that consumers feel satisfied and want to visit again. As a sustainability effort in culinary that Indonesia is proud of, it is proven that Customer Satisfaction and Physical Environment can significantly impact the Revisit Intention of culinary tourism in Braga, Bandung.